Internal colonization - Ėtkind, Aleksandr 1955-; Makarov, Vladimir 1975- (Cambridge, United Kingdom Polity Press, 2011)
This is a radically new account of Russia's cultural history. Etkind introduces the concept of 'internal colonization' in order to analyse the history of the Russian Empire, its' culture and its' literature.
Part I: The non-traditional orient. Less than one and double ; Worldliness. --Part II: Writing from scratch. Chasing Rurik ; To colonize oneself ; Barrels of fur. -- Part III: Empire of the Tsars. Occult instability ; Disciplinary gears ; Internal affairs -- Part IV: Shaved man's burden. Philosophy under Russian rule ; Sects and revolution ; Re-enchanting the darkness ; Sacrificial plotlines. -- Conclusion.
Keywords: Russia -- Civilization -- 1801-1917.; Russia -- Colonization; Russia -- Territorial expansion